The Effect of Motivation and Work Discipline on the Employee Performance at PT. Tunas Rental Thamrin Jakarta - Rahmi Hermawati; Arya Tirta Fadillah (PINISI Discretion Review, 2018)
The success of an organization is influenced by the performance of individual employees.The purpose of this research is to identify phenomenon and obtain empirical evidence as well as conclusion concerning the effect of motivation and discipline on the performance of employees at the PT. Tunas Rental (Branch Thamrin, Jakarta). The method used is a quantitative method with an associative approach. Total population in this study as many as 125 people. Samples taken as many as 95 people (respondens), based on the formula Slovin by using proportional stratified random sampling procedure. Data analysis uses validity test analysis, reliability test, classic assumption test, multiple regression analysis, correlation coefficient analysis, coefficient determination analysis, t test, and f test. From the results of simultaneous hypothesis testing, it can be concluded that motivation and work discipline have a positive and significant effect on employee performance with a coefficient of determination of 22%, while the remaining 78% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (12.970> 3.100), thus Ho is rejected and H3 is accepted. This means that there is a positive and significant effect simultaneously between motivation and work discipline on employee performance at PT. Tunas Rental